Free-Form Surfaces Design Using Reverse Engineering Depending on Cross-Sectional Design Method - A.A.Duroobi, Ahmed (Anbar Journal of Engineering Sciences, 2012)
This research presented a strategy for designing a particular set of surfaces, obtained by the technique of cross-sectional design. The surfaces considered were formed by sliding a Bezier curve (profile curve), and also this research describes an automatic procedure for selective identification of sampling points in reverse engineering applications using Coordinate Measurement Machine. In addition, Matlab program have been used in the present work so as to plot the curve sections of the surfaces using transformation matrices. UGS program have been also used to connect the sections that designed in Matlab program to get the final shape of the proposed surface. It can be concluded that the whole steps task which built in the present research can be programmed in a single block of the part program that’s from it can be create any curve or surface at minimum designing time.